أثر استراتيجية باير في اكساب مهارات التصميم الطباعي لطلبة معهد الفنون الجميلة بمادة فن الاعلان (Journal of the College of Basic Education, 2024)
The current research aims to provide the graphic design skills for the students of the Institute of Fine Arts - Diyala in the subject of advertisement art, where the research problem was identified with weakness among the students. A research designed by her that created her honesty and stability, and after teaching according to the Bayer strategy, she used the appropriate statistical methods and concluded that there is a great effect of teaching according to the strategy in increasing student achievement, and accordingly the researcher organized her scientific material in this modest study by formulating the research problem and its importance.The current research aims to identify the impact of the Bayer strategy on the achievement of the students of the Institute of Fine Arts in the subject of advertising art. The first chapter represents (the general framework of the research) and organizes the research problem and the importance and limits of the research, represented by the students of the Institute of Fine Arts, fourth grade, who study the art of advertising and define the terms contained in the title of the research. As for the second chapter, it includes the theoretical framework, representing the constructivist theory, skill, Bayer strategy, graphic design, advertising, and previous studies and their discussion. The third chapter includes a presentation of the research methodology and procedures. Where the researcher adopted the appropriate experimental design, defining the research community, selecting the sample and its homogeneity, equivalence procedures between the experimental and control research groups, adjusting the variables and building the research.